The "Calcium Paradox" and its Impact on Neurological and Psychiatric Diseases - Bergantin, Leandro Bueno; Caricati-Neto, Afonso (Cambridge Scholars Publishing, 2018)
This book extends the original concept of the ""calcium paradox"" discovery, herein compiling more than 300 references in the field of calcium ion (Ca2+/cAMP) signalling pathways, neurotransmission and neurodegeneration, and neurological and psychiatric diseases. In this second edition, novel illustrations and tables (highlighting current medicines for treating these diseases, including their mechanism of action) offer improved insights into the concepts for students and clinicians. The description of other neurodegenerative diseases (Spinal muscular atrophy, Amyotrophic Lateral Sclerosis and.